Analisis Penerapan Pengetahuan Orang Tua dalam Stimulasi Aspek Perkembangan Anak Usia Dini - Tiara Permata Bening; Ichsan Ichsan (Ideas Publishing, 2022)
Knowledge about early childhood development is urgent. Because through the knowledge of parents can provide maximum stimulation. The purpose of the study was to find out how parents knowledge, the application of parental knowledge in stimulating child development and the factors that influence the application of parental knowledge in stimulating child development. This research uses field study method. The result is that the knowledge of parents in the aspect of developing religious and moral values ​​is quite good, the physical motor aspect is sufficient, the cognitive aspect is lacking, the language and social emotional aspects are good. The stimulation provided in developing various aspects of child development is adjusted to the aspects. Except for cognitive development, the stimulation given by parents is not appropriate for their age. Factors that influence this include education, work and busyness, parental awareness of the importance of child development, problems children have, and digital media. Pengetahuan tentang perkembangan anak mulai dari usia dini merupakan hal penting. Hal ini karena pengetahuan orang tua dapat memberikan stimulasi dengan maksimal. Tujuan penelitian ini untuk mengetahui pengetahuan orang tua, penerapannya dalam stimulasi perkembangan anak, dan faktor yang berpotensi mempengaruhi penerapan pengetahuan orang tua saat menstimulasi perkembangan anak. Penelitian ini menggunakan metode studi lapangan. Hasil penelitian menunjukkan bahwa pengetahuan orang tua di dalam aspek perkembangan nilai agama dan moral cukup baik, aspek fisik motorik cukup, aspek kognitif kurang, aspek bahasa dan sosial emosional baik. Stimulasi yang diberikan dalam mengembangkan aspek anak disesuaikan dengan aspeknya. Kecuali perkembangan kognitif stimulasi yang diberikan orang tua belum tepat sesuai usianya. Faktor yang mempengaruhi hal tersebut meliputi pendidikan, pekerjaan, kesadaran orang tua, problem anak, dan media digital.